2014
DOI: 10.5209/rev_hics.2013.v18.44223
|View full text |Cite
|
Sign up to set email alerts
|

El cambio didáctico y sus consecuencias en el profesorado de matemáticas y ciencias.

Abstract: ResumenPara conseguir resultados más óptimos en los procesos de enseñanza-aprendizaje de las matemáticas y ciencias en la actualidad se propone la mejora de la formación de los profesores. Esta preparación tiene tres dimensiones: formación inicial de grado donde se adquieran los conocimientos necesarios, una formación pedagógica para además de tener el conocimiento saberlo transmitir y una formación permanente en metodologías y actualización de contenidos para poder responder de la forma más eficaz a las neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, they observed that the level of student participation in these types of classes was low. A note should be made that student participation is one of the main aspects on which new teaching methodologies are based [58]. A research study carried out in Indonesia, in which 67 primary school teachers participated, describes their perceptions during confinement, highlighting that one of the resources they used was internet videos due to their accessibility and the explanations they had regarding their content [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, they observed that the level of student participation in these types of classes was low. A note should be made that student participation is one of the main aspects on which new teaching methodologies are based [58]. A research study carried out in Indonesia, in which 67 primary school teachers participated, describes their perceptions during confinement, highlighting that one of the resources they used was internet videos due to their accessibility and the explanations they had regarding their content [59].…”
Section: Discussionmentioning
confidence: 99%